2008
DOI: 10.1186/1477-7819-6-87
|View full text |Cite
|
Sign up to set email alerts
|

Incidental littoral cell angioma of the spleen

Abstract: Background: Littoral cell angioma (LCA) is a recently described primary vascular neoplasm of the spleen that may be associated with other malignancies and may itself also have malignant potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 33 publications
1
27
0
1
Order By: Relevance
“…Symptomatic LCA is often treated by splenectomy, given that several case reports have identified its malignant potential [22,23]. Bearing in mind the immunological disorders which may follow a pediatric splenectomy (as in our first case), the additional spleens which were present in that particular child were left intact.…”
mentioning
confidence: 99%
“…Symptomatic LCA is often treated by splenectomy, given that several case reports have identified its malignant potential [22,23]. Bearing in mind the immunological disorders which may follow a pediatric splenectomy (as in our first case), the additional spleens which were present in that particular child were left intact.…”
mentioning
confidence: 99%
“…5,6 Desde la década de 1930, las células endoteliales que recubren los senos vasculares del bazo se consideraron únicas debido a la exposición tanto de las propiedades fagocíticas como hematopoyéticas. La neoplasia de estas células da como resultado la formación de ACL, que presenta características histológicas y moleculares consistentes con tipos de células epiteliales e histiocíticas.…”
Section: Discussionunclassified
“…Görg et al 16 reported 2 cases and reviewed 5 additional cases of littoral cell angioma in the literature; all cases were hyperechoic, and 6 (86%) were multiple lesions. However, in 20 cases of littoral cell angioma reported in the English literature, [3][4][5][6][7][8][9][10][11][12][17][18][19][20][21][22][23][24] 10 cases (50%) were hyperechoic, 10 (50%) were hypoechoic or isoechoic, and 12 (60%) were multiple lesions. In our study, 2 patients (29%) had multiple hyperechoic lesions, and 5 (71%) had solitary hypoechoic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]18,19 The lesions were avascular in 2 cases, hypovascular in 2 cases, and hypervascular in 1 case. In our study, the lesions were hypovascular in 4 cases and hypervascular in 3 cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation